Alvar Aalto. École supérieure polytechnique d'otaniemi
Se desarrolla la obra de la Universidad Politécnica de Otaniemi.
Keywords: AALTO, ALVAR; FINLANDIA; ESPOO; OTANIEMI; ARQUITECTURA EDUCACIONAL; UNIVERSIDADES